Mapping Stakeholders of Graduate Work-Readiness (GWR) - Nankervis, A.; Verma, P.; Dhakal, Subas P. (Springer, 2019)
Using stakeholder theory this chapter maps and identifies the key stakeholders associated with the process and evaluation of GWR. From a shared value perspective three key stakeholder groups are identified: higher education institutions who are responsible for developing the GWR attributes of their graduates; governments who are responsible for financing education and ensuring that there is an effective and efficient functioning of the labour market, including meeting current and future skill needs of the economy; and employers who require trained and accredited graduates that possess those attributes that enable them to transition into current and future job vacancies.